A meta-analysis of analgesic efficacy of opioids in the treatment of neuropathic pain - A., Preethi; M., Kulandaiammal (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Neuropathic pain is the most common form of chronic pain often associated with impaired quality of life due to its poor management. Tricyclic antidepressants, serotonin and norepinephrine reuptake inhibitors and calcium channel alpha 2 ligand agonist are preferred as first line therapy for neuropathic pain. Lignocaine patches and transdermal patches of capsaicin are used as second line agents. Moderate efficacy opioids like tramadol and strong opioids are recommended as second line and third line therapy for neuropathic pain respectively. Previous meta-analysis and systematic review shows inconsistent data and lacks reliability in getting conclusive results in opioids use in neuropathic pain. So, author conducted a meta-analysis to reanalyse the analgesic efficacy of opioid agonist for the treatment of neuropathic pain. Methods: Author searched Oxford pain relief data base, Google web, Embase, Medline and Cochrane library from February 2001 to November 2017 for articles related to analgesic efficacy of opioid agonist in neuropathic pain based on author’s selection criteria. Reference list of reviews were retrieved using Prisma Algorithm and analysed using REVIEW MANAGER 5 software. Results: Among 1108 publications searched, only 5 trials met the inclusion criteria. Primary outcome measure was proportion of participants reporting 50% of pain relief or better. In five trials, 305 patients treated with opioids and placebo/standard treatment for neuropathic pain, the number per treatment group ranges from 31 to 170 (median 50±5). The overall point estimate of risk difference was 0.17 (95% CI 0.02 to 0.33, P=0.026) translating to number needed to treat (Benefit) of 5.9 (3.0 to 50.0). Conclusions: In this meta-analysis, opioid agonist efficacy trials shown consistent analgesic efficacy and benefit over placebo/standard treatment in reducing neuropathic pain.